Analisis Perbandingan Kualitas Perangkat Lunak Pada Website Perguruan Tinggi Menggunakan Metode Webqual, Apache J-Meter, Dan Web Server Stress Tool - Chaswarina Nimas Maharani; Dedi Darwis (Jurnal Teknologi dan Sistem Informasi, 2023)
The college website is basically used to share information to the academics and the wider community, the college website sometimes experiences an error when accessed by many users, from this test it will be known to the college website server in a good state or not, and to find out the perception of users after Use a college website. Web Server Tool, Apache J-Meter and WebQual is used as a method for testing websites in college, from the results of testing the level of error is quite large occurring on college websites when many users access, average click time the value is said to be enough, website- College websites need to improve on the server section in order to receive a lot of good requests and loading time on the website can be reduced, some college websites need to improve in terms of display and information distributed. The results of this test can be concluded that websites in universities require functional care and server performance and in terms of display and information distributed, in order to make users easier when using or access websites.